2012
DOI: 10.1098/rsbl.2012.0522
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variability and acoustic signals: a multi-level approach in songbirds

Abstract: These authors contributed equally to this work.Among songbirds, growing evidence suggests that acoustic adaptation of song traits occurs in response to habitat features. Despite extensive study, most research supporting acoustic adaptation has only considered acoustic traits averaged for species or populations, overlooking intraindividual variation of song traits, which may facilitate effective communication in heterogeneous and variable environments. Fewer studies have explicitly incorporated sexual selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 17 publications
0
49
2
1
Order By: Relevance
“…While many studies do attempt to take the environment into account in some way (such as by classifying them as 'boreal' vs. 'tropical' forest or 'open' vs. 'closed' species), only two studies included here actually measured the habitat and acoustic features at their study sites (Irwin 2000, Singh & Price 2015, and another three used mean climate measures (Botero et al 2009, Medina & Francis 2012, Xing et al 2017. Fully to test the ecological hypotheses included in this review the field requires more studies that explicitly quantify the sound space available at varying latitudes and to determine whether more complex songs fill a wider swathe of that space.…”
Section: Future Directionsmentioning
confidence: 99%
“…While many studies do attempt to take the environment into account in some way (such as by classifying them as 'boreal' vs. 'tropical' forest or 'open' vs. 'closed' species), only two studies included here actually measured the habitat and acoustic features at their study sites (Irwin 2000, Singh & Price 2015, and another three used mean climate measures (Botero et al 2009, Medina & Francis 2012, Xing et al 2017. Fully to test the ecological hypotheses included in this review the field requires more studies that explicitly quantify the sound space available at varying latitudes and to determine whether more complex songs fill a wider swathe of that space.…”
Section: Future Directionsmentioning
confidence: 99%
“…Consequently, the marsh grassbird contributes another case of contradictory patterns to the literature and confirms that there are no simple explanations or clear general patterns (c.f. Byers 2011Byers , 2015Medina and Francis 2012).…”
Section: Complex Divergence Patterns Across Latitudementioning
confidence: 99%
“…Several comparative studies have confirmed positive correlations between song elaboration and latitude, both among (Catchpole 1982;Botero et al 2009) and within species (Collins et al 2009;Kaluthota et al 2016). However, there are also studies with contrasting results (Byers 2011(Byers , 2015Medina and Francis 2012) and more studies are needed for a better understanding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sexual dimorphism may arise as the result of natural selection (Shine 1989, Badyaev andHill 2003), sexual selection is frequently invoked as the main force driving these differences (Darwin 1871, Andersson 1994. In fact, degree of sexual dimorphism is a commonly used indicator of sexual selection intensity (Owens et al 1999, Nadeau et al 2007, Medina and Francis 2012, an assumption generally supported by correlations between sexual dimorphism and intensity of sperm competition (Bennett and Owens 2002), rate of evolution of genes involved in plumage coloration (Nadeau et al 2007), or degree of polygyny (Payne 1984, Dunn et al 2001; but see Burns 1998, Friedman et al 2009). …”
mentioning
confidence: 99%